The Public-Private Partnership - The Malaysian Experience as a Model- - Benlagha, Mohamed reda; Belmahdi, Tarek (Finance and Business Economies Review, 2022)
Public-Private Partnership (PPP) is one of the most basic modern tools that contribute to the promotion and provision of the needs of its communities by providing quality services in the light of its increasing demands. This has led many countries to pay more attention to this trend in order to satisfy the needs of its citizens. This study aims to present the Malaysian experience in the field of partnership between the public and private sectors. The study concluded that the partnership between the public and private sectors in Malaysia is an effective model, and has great importance on the economic and social levels